Factors Influencing Payment of Irrigation Service Fees - Budhi, Gelar Satya (Makara Human Behavior Studies in Asia, 2006)
This article attempts to identify factors affecting participation in payment of irrigation service fees. There are five variables comprising demographic and economic of land variables were tested to find the variables that influenced the participation significantly. The five variables tested consisted of age and formal education as demographic variables; land productivity, land size, and land tenure as the economic of land variables. The results showed that formal education (demographic variable) had positive relationship and land size (economic of land variable) had negative relationship with the participation. Positive relationship between formal education and participation in payment of irrigation service fees meant that the participation increased as farmers’ education increased. Meanwhile, negative relationship between land size and the participation in payment of irrigation service fees showed that the farmers’ participation would increase as the land size owned by farmers decreased. In other words, participation in payment of irrigation service fees was higher among farmers with small lands rather than that among farmers with large lands.